Testing the validity of a novel, conceptual, strength-based model in predicting resilient functioning in an UK-based, adolescent, student population: a prospective evaluation - Bastounis, A. (2019)
Introduction: Mental health problems in adolescence can be precursors of psychosocial problems in adulthood, increasing the likelihood for engaging in health-risk behaviours. Given that most of mental health problems remain untreated for years with subsequent repercussions for society and economy, governments have stressed the need to implement universal, resilience interventions early in adolescence. Adolescence is a pivotal developmental period, favouring the large-scale roll-out of universal, resilience interventions. Due to the inconsistent effects of these interventions in decreasing mental health problems and promoting resilience, their content and structure should be reconsidered. As such, it is vital to investigate the underpinning pathways between stress and resilient functioning.